The Drivers of Repurchase Intention During The Corona Pandemic: An Examination of Gender Difference - Wahyuningsih, Wahyuningsih; Nasution, Hanny; Yeni, Yulia H; Roostika, Ratna (ASEAN Marketing Journal, 2022)
Manuscript type: Research Article Research Aims: To examine the drivers of repurchase intention and test the difference between male and female consumers on the relationships between consumption value, satisfaction, and repurchase intention. Design/methodology/approach: This study employs a descriptive research design. Data were collected from 214 consumers who purchased food from the restaurant using the online application. Structural Equation Modeling has been employed to test the proposed hypotheses. Research Findings: This study finds that repurchase intention is driven by perceived consumption value and satisfaction for all consumers. The result suggests that male and female consumers perceived different perceptions of the relationships between consumption value, satisfaction, and repurchase intention. Theoretical Contribution/Originality: The findings of this study contribute to the body of knowledge in marketing literature by enlarging the linkage between consumer behavior and market segmentation theory. Understanding market segmentation, specifically based on gender differences, will help marketers formulate a better marketing strategy relevant to the market's characteristics. Practitioner/Policy Implication: Restaurant managers are suggested to increase their delivered consumption value, including functional value, social value, emotional value, safety value, and information value. Website providers are encouraged to increase delivered emotional value for consumers as they seek convenience in delivery service, transaction, and payment. Research limitation/Implications: This study was conducted in Indonesia using cross-sectional data; therefore, future research might replicate and enlarge the model of study to be implemented in a cross-cultural context using a longitudinal approach.